Low-impact development for impervious surface connectivity mitigation: assessment of directly connected impervious areas (DCIAs). Issue 10 (3rd October 2017) - Sohn, Wonmin; Kim, Jun-Hyun; Li, Ming-Han
Abstract : Urbanization increases directly connected impervious area (DCIA), the impervious area that is hydraulically connected to downstream drainage by closed pipelines. Although the benefits of low-impact development (LID) have been examined in other studies, its effect on alleviating DCIA levels has seldom been assessed. This study measured the DCIA of urban watersheds in Houston, TX, USA. Five land-use types were categorized and the contribution of LID facilities to reducing DCIA in each type was estimated by using Sutherland's equations. The results showed (1) DCIA in commercial areas was greater than that in residential areas, especially for big-box retailers; (2) the percentage of DCIA reduction by LID varied by land-use type; and (3) optimal combinations of LID application could maximize the effectiveness of DCIA reduction. The results contribute to prioritizing land-use type for implementing LID practices and providing local governments with a useful measure to estimate runoff volume.